2009
DOI: 10.1098/rspb.2009.0401
|View full text |Cite
|
Sign up to set email alerts
|

Individual and social discounting in a viscous population

Abstract: Social discounting in economics involves applying a diminishing weight to community-wide benefits or costs into the future. It impacts on public policy decisions involving future positive or negative effects, but there is no consensus on the correct basis for determining the social discount rate. This study presents an evolutionary biological framework for social discounting. How an organism should value future benefits to its local community is governed by the extent to which members of the community in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…These analyses demonstrate that scaled relatedness will in general decrease with group size (e.g. Aoki, 1982;Taylor, 1992;Taylor & Irwin, 2000;Roze & Rousset, 2004;Gardner & West, 2006;Lehmann, Perrin & Rousset, 2006;Johnstone & Cant, 2008;Sozou, 2009;Gardner, 2010;Ohtsuki, 2010;Van Dyken, 2010;Bao & Wild, 2012;Kuijper & Johnstone, 2012;Rodrigues & Gardner, 2012;Van Dyken & Wade, 2012). It is worth noting here that the size of the breeding group (deme) in island models may not be the same as the size of the social group in which helping interactions occur.…”
Section: (2) Lattice Models and Other Variations Of The Baseline Groumentioning
confidence: 89%
“…These analyses demonstrate that scaled relatedness will in general decrease with group size (e.g. Aoki, 1982;Taylor, 1992;Taylor & Irwin, 2000;Roze & Rousset, 2004;Gardner & West, 2006;Lehmann, Perrin & Rousset, 2006;Johnstone & Cant, 2008;Sozou, 2009;Gardner, 2010;Ohtsuki, 2010;Van Dyken, 2010;Bao & Wild, 2012;Kuijper & Johnstone, 2012;Rodrigues & Gardner, 2012;Van Dyken & Wade, 2012). It is worth noting here that the size of the breeding group (deme) in island models may not be the same as the size of the social group in which helping interactions occur.…”
Section: (2) Lattice Models and Other Variations Of The Baseline Groumentioning
confidence: 89%
“…As discussed in Section 1, the discount rate decreases in childhood. In adulthood, on the other hand, while still empirically inconclusive, Trostel and Taylor [28] and Read and Read [29] found that the discount rate increases with senescence 12 . The present study focuses on the biological discount rate ignoring the effect of social factors such as education, and may overestimate the discount rate in adulthood in modern human populations.…”
Section: Time Preferencementioning
confidence: 99%
“…evolutionary origin of time preference. More recently, technical similarities for studying aging in bio-demography and the intertemporal allocation in economics have allowed biologists, demographers and economists to enter this hybrid field, leading to the examination of how the time-discounting behavior relates to senescence (Sozou and Seymour [9]) and to intergenerational transfers (Chu et al [10]), why it is hyperbolic (Robson and Samuelson [11]), the rationale for social discounting (Sozou [12]), how it depends on age (Kageyama [13]), and how it relates to extrinsic mortality (Chowdhry [14]) 3 . To investigate the impatience of children, the present study follows this literature and extends Kageyama [13] by incorporating childhood, i.e., the growth period to maturity.…”
mentioning
confidence: 99%
“…Grafen 1984; Taylor 1992; Queller 1994; Taylor & Irwin 2000; West et al. 2007; Grafen & Archetti 2008; Johnstone & Cant 2008; Sozou 2009).…”
Section: Evolutionary Equilibrium Under the Joint Action Of Natural Sunclassified
“…Individuals not only may discount future rewards to self, or to their offspring, but are also likely to discount future rewards to other individuals living in their group or in other groups from the population. Social discounting involves applying a diminishing weight to group‐wide future benefits (Sozou 2009). As most natural populations tend to be spatially structured (Clobert et al.…”
Section: Introductionmentioning
confidence: 99%